ToxApp4nanoCELFI – integrated view on the safety assessment of nanocelluloses - Silva, Maria João (2022)
Background: The expanding production and application of cellulose nanofibrils (CNF) has increased the risk of human exposure (workers and consumers); It is mandatory to ensure the safety of CNF for human health and the environment in a costeffective way – relevant to public and occupational health and also to industries; Because CNF are nanofibers with a high aspect ratio like MWCNT and crocidolite, the main question is whether some of the CNF synthesized may have deleterious effects on human health; Limited toxicological data is available for CNF given that most studies have focused on bacterial or nanocrystalline celulose; A previous study by the team showed that a CNF produced by TEMPO-mediated oxidation of an industrial bleached Eucalyptus globulus kraft pulp was genotoxic to alveolar cells (Ventura et al., 2018); The assessment of potential toxic effects of the newly synthesized CNF must be addressed in an early phase of the value chain to allow changes to be made before the production scale up (the safer-by-design approach).